Klasifikasi Kesehatan Mental Mahasiswa dengan Algoritma J48 dan Hubungan Atribut Demografis serta Akademis - Cahyani, Evril Fadrekha; Aeni, Alfina Nur; Wahyuni, Irmawati Tri; Tarwoto, T (STIKOM Tunas Bangsa Pematangsiantar, 2024)
The college years are a period of significant development in various aspects, including physical, psychological, and intellectual growth. Students often face mental health issues such as depression, anxiety, and panic attacks, which frequently go untreated and can persist into adulthood. This study aims to analyze the mental health of college students using the J48 algorithm to classify the target attribute